Textile Strikes in Quebec: 1946, 1947, 1952 - Baillargeon, Denyse (Madeleine Parent: Activist, 2005)
Describes the strikes in the textile mills of Montreal, Valleyfield and Lachute that were led by Madeleine Parent and Kent Rowley in the post-World War II period, and the anti-communist purge of US-based unions that resulted in their dismissal from the United Textile Workers of America in 1952.
Keywords: Biography; Feminism; History; Parent; Madeleine; 1918-2012; Social conditions; Syndicalism; Women political activists